The Influence of Progressive Relaxation Technique on Blood Pressure in Hypertension Patients - Susanti, Susanti; Bistara, Difran Nobel (Jurnal Keperawatan Respati Yogyakarta, 2020)
One of the most common health problems in the community is hypertension. Hypertension is a circulatory system disorder that causes an increase in blood pressure above the normal value, which exceeds 140/90 mmHg. There are several ways to overcome hypertension by non-pharmacological methods, one of which is the Progressive Relaxation Technique. Progressive Relaxation Techniques are systematic techniques to achieve a state of relaxation that is used to reduce blood pressure in people with hypertension. The purpose of this study was to determine the effect of providing progressive relaxation techniques on blood pressure in patients with hypertension in the Wedi Baru Tambak Region in Surabaya. The research design used was pre-experimental with theapproach One Group Pre-Post Test Design. The population is 45 people with hypertension in Tambak Wedi Baru area taken bytechnique with Simple Random Sampling 40 people. The independent variable in the study was Progressive Relaxation Technique while Blood Pressure. Blood pressure measurement using progressive observation Pre-Post observation sheets. Data were analyzed using thetest Wilcoxon. The test results obtained the value of p value = 0.000 (Î± = 0.05) means that there is a difference in blood pressure before and after the intervention and the results of the mean there is the influence of blood pressure in patients with hypertension in Tambak Wedi Baru Region RT 03 Surabaya. The results of research that progressive relaxation is done to maintain blood pressure stability. It is recommended to be able to do Progressive Muscle Relaxation Therapy independently. in order to reduce blood pressure effectively and efficiently.